A COMMUNITY BASED PRIMARY HEALTH CARE APPROACH TO WATER, SANITATION, AND HYGIENE (WASH) IN RURAL NICARAGUA - Jafarian, Sohaila (My University, 2018)
Proper water, sanitation, and hygiene (WASH) practices are crucial to reduce disease in rural communities. In 2015, AMOS Health and Hope implemented a pilot program in the rural community of Banco de Sikia, Nicaragua that educated and empowered community health workers to promote improved WASH behavior. Baseline data for WASH practices in the community was collected via door-to-door knowledge, aptitude, and practices (KAP) surveys. Six members of the community volunteered to be trained as Water Promoters, each delivering monthly WASH education and counseling to between eight and twelve houses in the community. The Water Promoters’ WASH training was directed to address unhealthy behavioral practices that were identified through the baseline KAP surveys. In 2016, post-intervention KAP survey data was collected to assess overall impact of the Water Promoters in Banco de Sikia. The empowerment-based approach that was utilized was found to be highly effective in improving key KAP indicators while simultaneously decreasing the disease burden of the community. Based on these positive results, the program was extended to the community of El Bambu, Nicaragua in 2016. Baseline KAP surveys were conducted and were used to guide a new group of Water Promoter volunteers. To improve and enable data integrity, a handheld GPS device was used to collect the geographic coordinates of each home that was visited and associate the location with the name of the head of the household and the status of their water filter. We found the program to be highly successful in not only reaching a majority of the rural community members, but also in making healthy WASH behavior changes within the community. We anticipate this novel approach of implementing WASH training using community-based, primary health care principles to be an effective and valuable method of delivering WASH topics to the most affected areas around the world. To effectively gauge long-term impact, progress in WASH practice adoption should continue to be evaluated in these communities.
Keywords: health care; CBPHC; water; sanitation; hygiene; WASH; Nicaragua